Independent effects of the human circadian system and sleep/eating cycles on caloric intake in adolescents vary by weight status - David H. Barker; Mary A. Carskadon; Caroline Gredvig-Ardito; Chantelle N. Hart; Hollie A. Raynor; Frank A. J. L. Scheer (Proceedings of the National Academy of Sciences, 2025)
Late-day eating is linked to increased obesity risk; however, whether the endogenous circadian system independently influences caloric intake and if this control differs among individuals based on weight status is unknown. Here, we investigated in adolescents the independent roles of the endogenous circadian system and of the behavioral sleep/wake cycle (sleep/wake, fasting/eating, rest/activity, dark/dim light, social interaction, posture, etc.) on self-selected caloric intake using a Forced Desynchrony protocol. Fifty-one male and female adolescents across three weight status categories (24 with healthy weight, 13 with overweight, and 14 with obesity) completed the protocol where participants lived on seven 28-h sleep/wake cycles in dim light during wake and complete darkness during sleep. Results suggest that the circadian system and the behavioral cycle each affected caloric intake, with a decrease across the wake episode and an increase from circadian morning to circadian evening in caloric intake. The endogenous circadian rhythm in caloric intake showed a circadian peak-to-trough difference of 196 [CI 95% 164, 226] kcal per meal with peak timing of 296° [288°, 304°; equivalent to ~17:30 in these participants]. In those with overweight/obesity, more calories were consumed later in the waking episode and later in the circadian cycle, and with blunted amplitudes compared to those with healthy weight. Results implicate both the endogenous circadian system and the behavioral cycle in shaping the daily rhythm of food intake. Furthermore, these results help explain the increased drive for caloric intake toward the evening, especially in those at risk for obesity.